Leading Teachers’ Emotions Like Parents: Relationships Between Paternalistic Leadership, Emotional Labor and Teacher Commitment in China - Zheng, Xin; Shi, Xiao; Liu, Yuan (Frontiers in Psychology, 2020)
Emotional labor plays an essential role in school leadership and teaching, as principals and teachers undergo complex interactions with students, colleagues and parents. Although researchers have realized the influence of leaders’ behaviors on followers’ emotions in management and educational contexts, the relationship between leadership behaviors, teachers’ emotional labor and related organizational outcomes has been underexplored. As leadership and emotional labor are situated and influenced by cultural contexts, the current study focused on the relationship between teachers’ emotional labor strategies, multidimensional teacher commitment, and paternalistic leadership, a unique leadership type rooted in Confucianism. Paternalistic leadership is a style that combines strong authority with fatherly benevolence, which is prevalent in East Asia and the Middle East. A sample of 419 teachers was randomly selected to participate in a survey. The results showed that principals’ authoritarian leadership behaviors had negative influences on teachers’ commitment to the profession and commitment to the school. Benevolent leadership had positive effects on teachers’ commitment to students, commitment to the profession and commitment to the school. Teachers’ deep acting played positive mediating effects, while surface acting was a negative mediator. The results imply that school leaders could properly exert parent-like leadership practices to facilitate teacher commitment through managing teachers’ emotions.